Culinaria China : a celebration of food and tradition - Schlotter, Katrin ([Place of publication not identifed] : H.F. Ullmann Publishing, 2015)
"Tasting, smelling and enjoying China - explore the specialties of the metropolises and the regional cuisine: from the South of China, the melting pot of cuisine, to the rich coast provinces in the North, to the palace cuisine of Beijing all the way to the fiery-hot Szechuan dishes and adventurous dishes from the steppe. This thoroughly researched volume lifts the secrets of the Middle Kingdom: What for example hides behind dishes like blister soup", beggar's chicken" or even ants climbing a tree"? What does the day of a Chinese worker look like and how is a wedding celebrated? What does a big family in Beijing eat on the weekend and which viands are served to a pilgrim after his visit to a cloister? The authors of this book are sinologists and are well versed in China. They offer many exciting details about the history, customs and tradition as well as the modern life in this country, which changes daily and remains yet closely attached to its past.
Beijing -- Shandong -- Jiangsu -- Shanghai -- Anhui -- Zhejiang -- Fujian -- Guangdong -- Hong Kong -- Macau -- Yunnan -- Hunan -- Sichuan -- Gansu -- Xinjiang -- Inner Mongolia -- Heilongjiang.
Includes bibliographical references and index.
Keywords: COOKING, CHINESE